Exploring the success of regional bank mergers: Financial versus non-financial performance - Thomas M. Brunner-Kirchmair; Johann Burgstaller (German Economic Review (GER), 2025)
This study examines effects of mergers between Austrian banks from 2005 to 2018. Using matching techniques, we assess consequences for bank profitability and financial efficiency, as well as the impact on loan growth and a measure of social efficiency. Significant effects are observed in naive comparisons to non-merging banks, which almost entirely disappear after balancing with bank-level and environmental factors. This indicates that the average bank merger is neither value-decreasing nor value-enhancing. However, variation in individual merger success is huge and associated with several organizational and strategic factors, such as pursued cuts in personnel expenses or changes in market power.
Keywords: G21; G34; R51; 330; bank mergers; bank performance; cooperative banks; matching technique; merger success; savings banks